2013
DOI: 10.1080/01140671.2013.781039
|View full text |Cite
|
Sign up to set email alerts
|

Virus resistance of Australian pea (Pisum sativum) varieties

Abstract: Australian pea varieties were evaluated for virus resistance using spreader plots sown with Pea seed-borne mosaic virus (PSbMV)-infected seed and aphid inoculations with Bean leafroll virus (BLRV). Natural infections by Bean yellow mosaic virus (BYMV) and Soybean dwarf virus (SbDV) allowed also screening for these viruses. Complete PSbMV resistance was limited to a few varieties, but BYMV resistance was relatively frequent. No consistent ranking of partial PSbMV resistance or PSbMV seed transmission rates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…It was also found at a surprising high incidence in an evaluation for virus resistance in Australian field pea cultivars (van Leur, Kumari, et al, 2013), possibly resulting from the use of US cultivars as parents in the Australian pea breeding programs.…”
Section: Resistance To Potyvirusesmentioning
confidence: 99%
See 3 more Smart Citations
“…It was also found at a surprising high incidence in an evaluation for virus resistance in Australian field pea cultivars (van Leur, Kumari, et al, 2013), possibly resulting from the use of US cultivars as parents in the Australian pea breeding programs.…”
Section: Resistance To Potyvirusesmentioning
confidence: 99%
“…Baggett and Hampton (1991) did not exclude the possibility of additional, additive, genes for BLRV resistance. van Leur, Kumari, et al (2013) quantified BLRV resistance in Australian pea cultivars, but did not find immunity. Crampton and Watts (1968) in New Zealand concluded that resistance to pea leaf-roll/top-yellows (likely a combination of BWYV and SbDV) was based on additive and dominant genes.…”
Section: Resistance To Luteo- Polero- and Nanovirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of alternative hosts, epidemic development of PSbMV in commercial crops has to rely on seed transmission to survive crop free periods. In Australia, very high levels of PSbMV seed transmission have been found in several field pea cultivars (Coutts et al 2009;van Leur et al 2013) and incidences in pea crops were found to be related to infection rates in the seed used, both in experiments (Coutts et al 2009) and in commercial fields (Freeman et al 2013). Low levels of transmission through lentil seed has been found under experimental conditions (Coutts et al 2008), but not in commercial seed lots and PSbMV plant infection in lentil fields is invariable related to nearby infection in pea fields (Aftab and Freeman, unpublished results).…”
mentioning
confidence: 99%